Treinamento de membros superiores em cicloergômetro de pacientes com doença pulmonar obstrutiva crônica : revisão sistemática - Gonzaga, Luana Aparecida Vieira (2017)
Upper limb muscle training in patients with COPD has been recommended by pulmonary rehabilitation programs, due to the alterations caused by this disease, such as exercise intolerance, characterized by decreased muscular strength and endurance, with consequent increase in Muscle fatigue However, little is known about the effects and the ideal cycle ergometer training protocol to be applied to this population due to the scarcity of studies that address this theme. Objective: Collect evidence on the effects of upper limb training on cycle ergometer and bring together the main protocols used. Methods: Studies published between 1990 and March 2016 were searched in the electronic databases: PubMed, LILACS, Web of Science and Embase with the following combination of descriptors: chronic obstructive pulmonary disease OR cycloergometer OR upper limb Training OR supported training OR tolerance to Exercise OR strength OR strength. Results: A total of 2,927 studies were found and 8 studies were included. The results indicate a great variability of the temporal parameters, the methods of quantification of the load and the studied variables. Conclusion: The training on arm cycle ergometer lasts on average seven weeks, three times a week, with the session lasting in average 21 minutes. The load definition is established according to the Incremental Test of UL, defined as 60 to 80% of the peak load, with load progression performed according to patient tolerance. With the present review, it can be verified that the cycle ergometer training of MMSS promotes improved exercise tolerance and reduced dyspnea in patients with COPD.